The Effectiveness of Farming in the Method of Hydroponics - Atamurodov B. N; Ibodov I. N; Najmiddinov M. M; Safarov Sh. T; Najimov D. Q (International Journal on Human-Computing Studies, 2021)
Kidroponics is a method of growing plants in an artificial environment without soil. In this method, it is possible to achieve the cultivation of mainly vegetables, flowers, berries, greens for livestock and poultry, much more effective than other methods of watering and forming a glaze.